THE ANALYSIS OF STUDENTS’ ATTITUDE TOWARD THE USE OF PRINTED DICTIONARY IN TRANSLATING TEXT ON THE THIRD YEAR STUDENTS OF ENGLISH DEPARTMENT OF FKIP UMMY SOLOK - Riri Listia Dewi; Marsika Sepyanda; Risza Dwiputri (Universitas Mahaputra Muhammad Yamin, 2019)
This study was aims to know the attitude of students towards the use of printed dictionaries in the Translation class in the third year of English Department at 2017/2018 academic year. This research is motivated by problems faced by students in translation class. Students are often bored in the learning process, material of teaching does not improve the students’ critical thinking, the students have lack of background knowledge, and the students error in using dictionary. The problem can be solved by the lecturer by using printed dictionary as a media to translate text in the Translation class.The research method used in this study was descriptive quantitative. The subject of this study was all third year students of English Department at UMMY Solok at 2017/2018 academic year. The number of subjects in this study were 6 students. In collecting the data, researcher used questionnaire, in this questionnaire the students cloud tick (√) in the response column provided. In this case the researcher used 26 number of statements that correspond to 3 indicators and 13 sub-indicators. In the attitude indicator, the researcher divided into cognitive, affective and behavioral aspects. The results showed that the students’ attitude toward the use of printed dictionary in translating text based on three indicators that got good percentage (60,1%). Based on the result of the research, it could be guidance for English lecturer to using printed dictionary to teach the students in teaching Translation. It is hoped to make the lecturer know the advantages of printed dictionary as a tool to do translating the text. It is expected that the finding of this research can offer lecturer more information to teach Translation. For the students, they are must often to use printed dictionary to translate the text in Translation class.